Mekhong Cruise Servicing along the Mekhong River in Luangprabang Heritage City, Luang Prabang Province - SOUKANYA, Kongkeo; SOUTHIVONG, Phengphanh; DONSAVANH, Beun; INTHALEUXAY , Sysomphou; BOUAPHAKEO, Pazeun; BOUAPHAVONG, Douangta (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research study to providing boat tours along the river. The Luang Prabang Provincial Boat Association has 3 locations: Ban Don Nui Port, Luang Port and Wat Nong Port. The case study of Wat Nong Port which includes to study the satisfaction of tourists to the service of guided tours along the Mekong River. It is a quantitative and qualitative study in collecting data from 180 questionnaires, using descriptive statistics and giving actual meaning from data analysis to be accurate and precise. The results of the study on the satisfaction of tourists to the service of guided boats along the Mekong River from the analysis of the results of the study shows that tourists are satisfied with all 7 aspects: there is satisfaction of tourists to the service of the guided boat, an average of 3.98, the confidence of customers in the service of the guided boat is at a very high level, an average of 3.92, there are physical things offered to tourists who come to use the service at a very high level, an average of 3.77, the service of the staff towards the satisfaction of the tourists is at a high level, an average of 3.66, the satisfaction of the service of the staff inside the boat is at a very high level Average 3.59, satisfaction with other service charges of tourists is at a high level, average 3.67 and things that should be improved in the service of boat tours along the Mekong River at a high level, average 3.47. Also, the customer also offers to make a map to show the location of the boat service for convenience, providing information throughout the travel period and saving time in finding the place.